Implementation of Problem Based Learning Model with Animated Video Media to Improve Student Learning Outcomes - Astuti, Parida Dwi; Dianasari, Dianasari; Fadly, Aris (FKIP - Universitas Riau, 2025)
This research was motivated by the low learning outcomes of Class VB students at SD Negeri 1 Gesik in the Pancasila Education subject, particularly on the topic the diversity of Indonesian culture. The purpose of this study was to improve student learning outcomes through the implementation of the Problem Based Learning model assisted by animated video media. This research is a classroom action research study that follows the Kemmis and Taggart model, which consists of the stages of planning, action, observation, and reflection. The subjects of this study were 31 students of Class VB at SD Negeri 1 Gesik. The study was conducted in two cycles. The results showed that in the first cycle, students' mastery of the learning material reached a completeness percentage of 39%, with 12 students achieving the learning criteria. In the second cycle, there was a significant improvement, with 90% of students 28 students achieving learning completeness. Therefore, it can be concluded that the application of the Problem Based Learning model supported by animated video media can enhance student learning outcomes in the Pancasila Education subject for Class VB at SD Negeri 1 Gesik.